Complex Geodetic Monitoring of the Massive Sports Structures by Terrestrial Laser Scanning - Shults, Roman; Seitkazina, Gulnur; Annenkov, Andriy; Demianenko, Roman; Soltabayeva, Saule; Kozhayev, Zhenis; Orazbekova, Gulizat (Civil Engineering Journal, 2025)
The paper describes the rigorous approach to studying and analyzing the results of geodetic monitoring of massive sports structures. The monitoring results for two ski jumps in Almaty, Republic of Kazakhstan, are considered a case study. The suggested approach is based on the combined use of geodetic measurements and their comparative analysis with the structural analysis results of the structure using the finite element method. The structural analysis was carried out for various loads and their combinations, e.g., dead weight, snow load, wind load, etc. The article's aim is twofold. The first is to develop an appropriate algorithm and technology to accomplish geodetic monitoring, including the assignment of allowable monitoring accuracy. This goal was achieved by the results of structural analysis that helped to determine the allowable displacements and zones of maximum stress. These values defined the necessary observation accuracy and the places for the deformation targets' installation. Thus, the appropriate monitoring network around the complex of ski jumps was created. Geodetic monitoring was carried out using terrestrial laser scanning. Four observation epochs were conducted from autumn 2020 until summer 2022. The second aim is to analyze the monitoring results to determine the actual structure displacements and make conclusions concerning the allowance of these displacements for further structure exploitation. The monitoring results were studied using the structural analysis and B-spline displacement simulation. The results demonstrated no significant displacements of the ski jump ramps. The displacements for landing hills reached 60 mm, which is the allowable value. Doi: 10.28991/CEJ-2025-011-03-05 Full Text: PDF